Feed Preferences of Yellow-crested cockatoo (Cacatua sulphurea sulphurea) in Pasoso Island, Central Sulawesi - Ani Mardiastuti; Burhanuddin Masy’ud; Yeni A. Mulyani; Moh. Ihsan (Pusat Penelitian dan Pengembangan Hutan, 2021)
The yellow-crested cockatoo (Cacatua sulphurea sulphurea) is a sub-species of Cacatua sulphurea widely distributed in Sulawesi and several surrounding islands including Pasoso. Currently, the population has decreased and is categorized as critically endangered, hence, conservation measures are needed. One conservation approach is by understanding feed preference as an important aspect of improving survival. This study, then, aims to determine the feed preferences of yellow-crested cockatoos on Pasoso Island. It was conducted from April-September 2019 using data on the regeneration of forage plants obtained with a 20 m x 20 m plot, while feed preference data were taken using the focal animal sampling method. Furthermore, the data obtained were analyzed using the Jacobs preference index and the results showed that Buchanania arborescens is the type of forage plant that is most consumed. Based on the Jacobs category, it was known that B. arborescens and Ficus benjamina were the preferred types of feed, while Aglaia argentea was less preferred. However, the most preferred feed do not regenerate in the primary forest and had low regeneration in the ecotone habitat type, and an effort to develop the habitats by planting more B. Arborescens is necessary.